Fabrication of polyurethane composites via reactive binder jetting (RBJ) using a dual-ink binding system - Torres, Arielle Colette (2025)
The high processing temperatures traditionally required for Additive Manufacturing (AM) often degrade polymer powders, limiting part performance and recyclability. Reactive Binder Jetting (RBJ), a novel AM process, addresses these challenges by utilizing a dual-ink binding system that facilitates powder consolidation at ambient temperatures. This eliminates the need for energy-intensive equipment, such as lasers or heaters, enabling sustainable manufacturing of complex, functional parts.